Pelatihan dan Pembinaan Keterampilan Renang melalui Pengenalan Stretching (Statis dan Dinamis) pada Binaan Siswa PRSI Jakarta Utara - Prawira, Asrori Yudha (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Sports Coaching For Students trainees and coaching is very important to direct the talents and interests of the students trainees and coaching precisely in Sports activities, especially swimming sports, so that the students trainees and coaching can take advantage of the empty time after school with good sports activities and as a place to further develop swimming skills, fitness, and health. Swimming Sports training and coaching can also prepare students for training and coaching, the community, especially the younger generation, designs skills and physical fitness in general and thoroughly and specifically, which means including students to be able to compete and compete in sports achievements, as well as develop their best swimming skills to strive to achieve them, and swimming sports can arise and be favored by the community with participating students training and coaching to develop swimming, fitness, and health skills. In the implementation of this PKM training and coaching, we want to convey for elementary, junior high, and high school students who have been coordinated into prsi north Jakarta guidance to better understand the systematic training and stages starting from the style in swimming and advanced techniques for them, students can get to know the occurrence of people who are prepared to become upholsterers and competitors of swimming sports clubs out there. Furthermore, in order to continue to provide training and coaching on the development and progress of sports, especially swimming sports and target the publication output of accredited national journals.